Reconstructing Abusive Guardianship through a Mubādalah-Based Child Protection Prototype: A Comparative Study of State Intervention in Indonesia and Malaysia - Muhammad Irfan Bin Mohd Nasruddin; Yayan Indriana (Journal of Islamic Mubadalah, 2026)
This article examines abusive guardianship in cases of sexual violence against children, in which parents or guardians who are supposed to provide protection instead become sources of threat to the victim’s safety. Its objectives are to analyze the revocation of guardianship in Indonesia, compare it with child protection mechanisms in Malaysia, formulate a child protection model based on mubādalah, and develop the MAPAN-Mubādalah Prototype. This study employs a qualitative method using a socio-legal case study design and a comparative approach. Primary data were obtained through interviews, observations, and documentation, while secondary data were derived from court decisions, Indonesian and Malaysian regulations, Islamic family law literature, and child protection documents. The analysis draws on mubādalah, maṣlaḥah mursalah, and law as a tool of social engineering. The findings indicate that the revocation of guardianship reconstructs the authority of the guardian into a mandate of protection; the comparison between Indonesia and Malaysia underscores the importance of cross-institutional state intervention; the child protection model must integrate victim recovery, restrictions on guardianship authority, and state responsibility; and the MAPAN-Mubādalah Prototype offers a framework for detection, risk assessment, intervention, safe caregiving, monitoring, and policy reform. This article recommends technical guidelines, risk assessment, and institutional coordination to strengthen sustainable child protection policy reform in both Muslim-majority countries.